2012
DOI: 10.1021/ja301691j
|View full text |Cite
|
Sign up to set email alerts
|

Multifluorescently Traceable Nanoparticle by a Single-Wavelength Excitation with Color-Related Drug Release Performance

Abstract: Monodisperse and nanometer-sized periodic mesoporous organosilicas co-doped with fluorescence resonance energy transfer cascades composed of triple fluorophores at various ratios were prepared. These nanoparticles exhibit multifluorescent emissions by a single-wavelength excitation and were designed for the application as multichannelly traceable drug carriers. Different from the hydrophilic framework of inorganic mesoporous silica and hydrophobic framework of mesoporous carbon, these multifluorescent nanopart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 17 publications
0
44
0
Order By: Relevance
“…[14][15][16][17] For example, Thiel and co-workers 15 generated a PMO material that successfully combined two antagonistic functional groups in a single PMO material, that is, one type of functional group was located in the framework walls and another functional group was directed to the pore channels. The resulting materials possess a hydrophobic phenylene layer and a hydrophilic propylamine layer.…”
Section: New Synthesis Routes and New Precursors For The Preparation mentioning
confidence: 99%
See 1 more Smart Citation
“…[14][15][16][17] For example, Thiel and co-workers 15 generated a PMO material that successfully combined two antagonistic functional groups in a single PMO material, that is, one type of functional group was located in the framework walls and another functional group was directed to the pore channels. The resulting materials possess a hydrophobic phenylene layer and a hydrophilic propylamine layer.…”
Section: New Synthesis Routes and New Precursors For The Preparation mentioning
confidence: 99%
“…The obtained material possesses molecular periodicity even with higher loading of the thiol functional precursor (67 mol % in the initial reaction mixture). Zhang and co-workers 16 synthesized nanometer-sized PMO materials using bridged organosilane precursors with three types of different functional groups (fluorophores) located in the mesopore walls. The obtained materials show multifluorescent emission by single-wavelength excitation.…”
Section: New Synthesis Routes and New Precursors For The Preparation mentioning
confidence: 99%
“…It is reported that the integration of organic and inorganic fragments can endow the obtained hybrid materials with mechanical stability, hydrothermal stability, tailored surface polarities, and even good biocompatibility for different applications, such as catalysis, energy conversion, drug delivery, and so on. [34][35][36][37][38] However, to the best of our knowledge, there is no report about synthesizing yolk-shell spheres in which the core and shell are made of inorganic-organic hybrid material. Overall, it remains a grand challenge to fabricate monodisperse yolk-shell structures with tunable size, accessible ordered mesochannels, inorganicorganic hybrid framework by a facile approach.…”
Section: Doi: 101002/adma201400136mentioning
confidence: 99%
“…[ 286 ] Bissilylated organosilica precursors, including biphenyl (Biph) ( R 1 ), anthracene (Anth) ( R 2 ), and naphthalimide (Naph) ( R 3 ), were initially synthesized via different chemical reactions ( Figure 28 a), which were further co-condensed with TEOS to form MONs with fl uorescent frameworks. Excited by single-wavelength light, these MONs showed multifl uorescent emission because of the consecutive FRET processes among Biph, Anth, and Naph (Figure 28 b).…”
Section: Mons For Bioimagingmentioning
confidence: 99%